2020
DOI: 10.3390/catal10030322
|View full text |Cite
|
Sign up to set email alerts
|

Pt Modified Heterogeneous Catalysts Combined with Ozonation for the Removal of Diclofenac from Aqueous Solutions and the Fate of by-Products

Abstract: The degradation of the pharmaceutical compound diclofenac in an aqueous solution was studied with an advanced oxidation method, catalytic ozonation. Diclofenac was destroyed in a few minutes by ozonation but several long-lasting degradation by-products were formed. For this reason, the combination of heterogeneous catalysts and ozonation was applied to eliminate them completely. The kinetics of the diclofenac degradation and the formation of by-products were thoroughly investigated. Loading of Pt on the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Both processes are accompanied by high operating expenses like pre-treatment and post-treatment [ 20 , 21 , 22 ]. Advanced oxidation processes (AOPs, like photocatalysis, photo-Fenton, ozonation or electrochemical oxidation) are highly discussed and investigated processes to eliminate micropollutants from water [ 23 , 24 , 25 , 26 ]. Reactive oxygen species (hydroxyl radicals, hydrogen peroxide, ozone, and superoxide anion radicals) are generated and completely mineralize micropollutants with a low selectivity to carbon dioxide, water, and inorganic ions or acids.…”
Section: Introductionmentioning
confidence: 99%
“…Both processes are accompanied by high operating expenses like pre-treatment and post-treatment [ 20 , 21 , 22 ]. Advanced oxidation processes (AOPs, like photocatalysis, photo-Fenton, ozonation or electrochemical oxidation) are highly discussed and investigated processes to eliminate micropollutants from water [ 23 , 24 , 25 , 26 ]. Reactive oxygen species (hydroxyl radicals, hydrogen peroxide, ozone, and superoxide anion radicals) are generated and completely mineralize micropollutants with a low selectivity to carbon dioxide, water, and inorganic ions or acids.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be concluded that the electrochemical process is more effective under acidic conditions compared to alkaline conditions. These results suggest that the production rate of radicals for reducing organic pollutants in wastewater is higher in acidic solutions compared to alkaline solutions [35]. However, it is important to note that any increase in acidity should be carefully managed in consideration of the coating applied on the anode and cathode to prevent corrosion of these coatings [36].…”
Section: Electrolysis Time Effectmentioning
confidence: 98%
“…The catalyst activity was enhanced via metal loading; however, overloading the metal can block the pores and active sites of the catalysts, resulting in a dramatic decline of the catalytic activity. Consequently, the metal content was kept small for most of the synthesized catalysts [38]. The Cu, Ni, Pd, and Fe metal contents in the metal-modified catalysts were analyzed using energy-dispersive X-ray microanalyses (EDXA); the analysis was performed three times for each catalyst, and the average amount was calculated and presented in Table 2.…”
Section: Nitrogen Physisorptionmentioning
confidence: 99%